Treatment with DNases rescues hidden neutrophil elastase from aggregated NETs - Podolska, Malgorzata; Mahajan, Aparna; Hahn, Jonas; Knopf, Jasmin; Maueröder, Christian; Petru, Lenka; Ullmann, Marc; Schett, Georg; Leppkes, Moritz; Herrmann, Martin; Munoz, Luis Enrique; Schauer, Christine (Journal of Leukocyte Biology, 2019)
The release of neutrophil extracellular traps (NETs) is one of the weapons neutrophils have in their armory. NETs consist of extracellular chromatin fibers decorated with a plethora of cytoplasmic and granular proteins, such as the antimicrobial serine protease neutrophil elastase (NE). Because the first description of NETs as beneficial to the host, reports on their double-faced role in health and disease have considerably increased recently. On one hand, NETs reportedly trap and kill bacteria and also participate in the resolution of the acute inflammation associated with infection and with tissue damage. On the other hand, numerous negative aspects of NETs contribute to the etiopathogenesis of autoimmune disorders. Employing soluble and solid fluorescent substrates, we demonstrate the interaction of NE with aggregated NETs (aggNETs), the limitation of its enzymatic activity and the containment of the enzyme from surrounding tissues. These events prevent the spread of inflammation and tissue damage. The detection of DNase 1-dependent elevation of NE activity attests the continuous presence of patrolling neutrophils forming NETs and aggNETs even under conditions physiologic conditions.
CRIS-Team Scopus Importer:2019-09-17
Keywords: aggregated NETs; DNase 1; NETs; neutrophil elastase; neutrophils